WAYS TO IMPROVE THE PROFESSIONAL AND METHODOLOGICAL COMPETENCE OF FUTURE GEOGRAPHY TEACHERS BASED ON AN INTEGRATIVE APPROACH (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines ways to improve the professional and methodological competence of future geography teachers through the implementation of an integrative approach in pedagogical higher education. The relevance of the study is determined by the increasing requirements for geography teachers to combine subject knowledge, pedagogical skills, methodological competence, digital literacy, geographical thinking, research abilities, and interdisciplinary interaction in their professional activities. The article theoretically substantiates the importance of integrating geographical, pedagogical, psychological, methodological, digital, and practical components in the preparation of future geography teachers. Particular attention is paid to interdisciplinary integration, practice-oriented learning, project-based activities, problem-based learning, digital geographic technologies, fieldwork, geographic information systems, collaborative learning, and reflective practices. The proposed approach is aimed at creating an integrated educational environment in which students can apply theoretical geographical knowledge to authentic pedagogical situations and develop the ability to design, implement, evaluate, and improve geography lessons. The study emphasizes that professional and methodological competence should be developed systematically rather than through isolated academic disciplines. An integrative model combining motivational-value, cognitive, practical-activity, technological, communicative, and reflective components can contribute to the gradual formation of professionally prepared geography teachers capable of responding effectively to contemporary educational requirements. The findings provide a methodological basis for improving teacher education programs in pedagogical universities and strengthening the connection between university-based theoretical preparation and school-based professional practice.